Islet Transplantation Provides Superior Glycemic Control With Less Hypoglycemia Compared With Continuous Subcutaneous Insulin Infusion or Multiple Daily Insulin Injections. Issue 6 (June 2017) - Holmes-Walker, Deborah Jane; Gunton, Jenny E; Hawthorne, Wayne; Payk, Marlene; Anderson, Patricia; Donath, Susan; Loudovaris, Tom; Ward, Glenn M; Kay, Thomas WH; O'Connell, Philip J
Abstract : Background: The aim was to compare efficacy of multiple daily injections (MDI), continuous subcutaneous insulin infusion (CSII) and islet transplantation to reduce hypoglycemia and glycemic variability in type 1 diabetes subjects with severe hypoglycemia. Methods: This was a within-subject, paired comparison of MDI and CSII and CSII with 12 months postislet transplantation in 10 type 1 diabetes subjects referred with severe hypoglycemia, suitable for islet transplantation. Individuals were assessed with HbA1c, Edmonton Hypoglycemia Score (HYPOscore), continuous glucose monitoring (CGM) and in 8 subjects measurements of glucose variability using standard deviation of glucose (SD glucose) from CGM and continuous overlapping net glycemic action using a 4 hour interval (CONGA4). Results: After changing from MDI to CSII before transplantation, 10 subjects reduced median HYPOscore from 2028 to 1085 ( P < 0.05) and hypoglycemia events from 24 to 8 per patient-year ( P < 0.05). While HbA1c, mean glucose and median percent time hypoglycemic on CGM were unchanged with CSII, SD glucose and CONGA4 reduced significantly ( P < 0.05). At 12 months posttransplant 9 of 10 were C-peptide positive, (5 insulin independent). Twelve months postislet transplantation, there were significant reductions in all baseline parameters versus CSII, respectively, HbA1c (6.4% cf 8.2%), median HYPOscore (0 cf 1085), mean glucose (7.1 cf 8.6 mmol L −1 ), SD glucose (1.7 cf 3.2 mmol/L), and CONGA4 (1.6 cf 3.0). Conclusions: In subjects with severe hypoglycemia suitable for islet transplantation, CSII decreased hypoglycemia frequency and glycemic variability compared with MDI whereas islet transplantation resolved hypoglycemia and further improved glycemic variability regardless of insulin independence. Abstract : This small single-center study suggests that in selected patients with severe hypoglycemia and large glycemic variability, islet transplantation provides superior glycemic control and reduction in hypoglycemia compared to continuous subcutaneous insulin infusion or multiple daily insulin injections.